Study Of Concrete Mixture Using Sea Sand With Fresh Water and Sea Water Cure - Arsyad, Febriansyah; Lakawa, Irwan; Ilham, Vickky Anggara; Hakiman, Hakiman (Sultra Civil Engineering Journal (SCiEJ), 2023)
The purpose of this study was to (1) analyze the characteristics of fresh concrete mixed with sea sand (2) to analyze the compressive strength of sea sand concrete with fresh water and sea water curing. In this study, the specimens used were 21 cylinders with a job mix design plan of f'c 25 MPa with a curing duration of 7 days, 14 days, and 28 days. At the age of 7 and 14 days the compressive strength of fresh water curing was 30.29 MPa and 33.12 MPa higher than seawater curing 29.02 MPa and 32.13 MPa, while at 28 days the compressive strength of seawater curing was 37. 08 MPa compared to fresh water curing of 33.97 MPa. Sea sand concrete has a very good quality compared to normal concrete and sea sand can be used in construction projects by taking into account the specifications in accordance with the Indonesian National Standard (SNI).